Computational Insights Into the Influence of Substitution Groups on the Inclusion Complexation of β-Cyclodextrin - Yan, Xianghua; Wang, Yue; Meng, Tong; Yan, Hui (Frontiers in Chemistry, 2021)
Cyclodextrins (CDs) and their derivatives have good prospects in soil remediation application due to their ability to enhance the stability and solubility of low water-soluble compounds by inclusion performance. To investigate the effect of different structural properties of cyclodextrin and its derivatives on the inclusion complexation, molecular dynamic (MD) simulations were performed on the inclusion complexes formed by three kinds of CDs with polycyclic aromatic hydrocarbons (PAHs). Based on neutral β-CD, the other two CDs were modified by introducing substitutional groups, including 2-hydroxypropyl and sulfonated butyl (SBE) functional groups in the ring structure, called HP-CD and SBE-CD. MD results show that PAH can merely enter into the cavity of SBE–β-CD from its wide rim. The substitutional groups significantly affect the structure of CDs, which may also cause the flipping of the glucose units. However, the substitutional groups can also enlarge the volume of the hydrophobic cavity, resulting in a tight combination with the guest molecules.